PENINGKATAN MOTORIK HALUS SISWA TK CENDRAWASIH MELALUI PSIKOEDUKASI DENGAN METODE LEARNING BY GAME - Nasywa Putri Aurora; Purwantini, Lucky; Maysaroh Chairunnisa, Nurlaila (Universitas Islam 45 Bekasi, 2024)
Early childhood is children between the ages of 0 and 8, and early childhood is children between the ages of 3 and 6. Development is the increasing ability to perform more complex functions and structures of the body in a systematic and predictable manner, as a result of the maturation process. Motor development is a very important component of development in a child's life. Play is an important activity in a child's life. This psychoeducational method uses teaching methods to see the child's development of fine motor skills, as well as learning by games which aims to improve the child's fine motor skills, to make learning a fun experience. The results of the paired sample t-test before and after the treatment of fine motor training with the learning by game method obtained significant differences in the development of fine motor skills before and after treatment.